The Application of Literacy by Using Storybook in Elementary School - Wahab, Isnaeni; Amaliyah, Nurhadifah (International Journal of Elementary Education, 2021)
Literacy is one way to build and develop children's thinking power which is important for students. However, students' literacy habits are still low. This study aims to obtain information about the application of literacy culture at the school, and the application of literacy using story book for students. This study uses a qualitative descriptive approach with a survey method. The subjects of this study were students of Elementary school. Data collection techniques through observation, interviews and documentation. Data analysis through the stages of data reduction, data presentation, and drawing conclusions. The results showed that literacy activities at the school had been implemented with literacy fifteen minutes before class and used every corner of the school to read, while the implementation of literacy using story books was done by inviting students to read books with various story titles. It can be said that Kartika Elementary School already has a good literacy program and the application of literacy using story books is able to invite students to retell the story and take the stories presented.